The Development of E-Learning Using Multimedia-Based GIS E-Modules - Supuwiningsih, Ni Nyoman; Parwati, Ni Nyoman; Suharta, I Gusti Putu; Tegeh, I Made (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The aim of this research is to develop an interactive, interesting, effective, and fun multimedia-based e-module for the Geographic Information Systems (GIS) course, which can be accessed online so that it can improve student learning outcomes in e-learning via Moodle LMS. The research method employed is the Research and Development (R&D) method. The research method used is the research and development method, which has been modified by Sukmadinata and consists of a preliminary study stage, a model development stage, and a model test stage. The data used in this research is primary data, a population of teaching lecturers who are experts in teaching Geographic Information Systems courses as an e-module trial. The second primary data is the respondent population of ITB STIKOM Bali students who took the Geographic Information Systems course. The sample used in this study was a simple random sample of students registered to take these courses. The data collection technique used in this research used a Likert scale questionnaire instrument for e-module testing. The questionnaire analysis technique uses the feasibility percentage formula. To determine the effectiveness of the e-module, give a test to a sample of students before and after using the e-module by using the N-gain formula in data analysis. The research findings indicate that the e-module is suitable for use as a learning resource, as it received a positive evaluation from the lecturers who used it, with an average score of 48.5 or 88.2% in the "excellent" category based on Likert scale responses in the questionnaire. Additionally, the e-module is effective for student learning, as evidenced by the N-Gain score of 0.74, with a value greater than 0.7, indicating a high level of effectiveness.